Sustainable Jute-Based Composite Materials : Mechanical and Thermomechanical Behaviour - Jabbar, Abdul (Springer International Publishing : Imprint: Springer, 2017)
This book shows how jute waste is collected from industry and used as a cheaper source to extract and use cellulose. Novel environment-friendly methods are explored for surface modification of natural fibers. The advantages of using biocomposites are listed and the author shows how they can be used effectively as secondary structural parts.
Keywords: Materials science.; Textile industry.; Nanotechnology.; Ceramics.; Glass.; Composites (Materials).; Composite materials.; elektronické knihy; electronic books